The genus Birdantis Stål in Australia (Hemiptera: Fulgoromorpha: Fulgoridae) - Constant, Jerome (Zootaxa, 2011)
Three new species of Birdantis Stål, 1863, B. virginiae n. sp., B. goemansi n. sp. and B. mouldsi n. sp. are described from Queensland, Australia. The species are endemic in Australia and compared to the other species of the mainly Papuan genus. Male genitalia and habitus are illustrated. Distribution maps and an identification key are given.